Determinant Factors Of Directors’ Remuneration: A Study On Malaysia Equity Market - Chong, Hai Hsiong (2014)
Bursa Malaysia is one of the most important stock exchange centers in ASEAN. The success and attractiveness of a stock exchange market relies on the stock price performance listed on the stock exchange. To propel Malaysia to become a high income nation, talented executive directors with great leadership skill is one of the crucial factor. In Malaysia, studies of executives’ remuneration, firms’ attributes and performance are always the key focus. Some of the area which lack of attention is the characteristic of executive directors and also ownership characteristics of a firm. Another factor that received little attention is the dividend payout policy of the firm in relationship to the executive directors’ remuneration.